Case report: Multiple gastrointestinal perforations in a rare musculocontractural Ehlers–Danlos syndrome with multiple organ dysfunction - Qian, Huitao; Zhou, Tao; Zheng, Nan; Lu, Qiulun; Han, Yi (Frontiers in Genetics, 2022)
Ehlers-Danlos syndrome (EDS) is a group of connective tissue disorders which are inheritable and characterized by varied manifestations and genetic causes. EDS is currently classified into thirteen subtypes. The clinical manifestations for EDS are mainly presented with joint hypermobility, skin hyper extensibility and tissue fragility. Herein, we report a case of multiple gastrointestinal perforations with a rare combination of vascular and musculocontractural EDS subtypes. A 36-year-old male with congenital equinovarus deformity was admitted to hospital because of aggravation of this deformity for more than one year. Before the period of in-hospital, ear perforation was performed in his childhood. At the beginning of in-hospital stay, he received equinovarus correction surgery, fourth toe osteotomy and external fixation for right foot during hospitalization. The patient developed intestinal perforation at splenic flexure of colon 10 days after the right foot operation, then were treated with partial colectomy and proximal fistulostomy. 10 days laters, he received exploratory laparotomy and gastric repair because of a large gastric perforation. During the period of his in-hospital stay, multiple organ dysfunction was observed involving heart, kidney, liver and intestines. Genetically, whole-exome sequencing was performed with him, and then the site mutation was verified with Sanger sequencing analysis. The patient had experienced multiple gastrointestinal perorations after the deformity correction surgery during his hospital stay. And then multiple organ dysfunction and fragile soft tissues was occured. Genetically, whole-exome sequencing was performed, identifying that there is a site mutation in CHST14 (NM_130468.3) c.883Cysfsperscri5 in this patient. Furthermore, the homozygous deletion of T and T at position 883 and 884 of CHST14 was verified by Sanger sequencing, and the mutation in this site was not observed in 100 healthy control. Our report shows that unanticipated multiple tissue perforations can occur in EDS patients. In this case, a complex of vascular and muscularcontractural EDS is observed with multiple organ dysfunction. This finding fundamentally redefines what is known about the natural history of EDS patients. Vigilance should be maintained in the thousands of EDS patients for higher possibilities of multiple organ dysfunction, gastrointestinal and soft tissue perforations, especially after long-term sedated bed stay.